2005
DOI: 10.1186/1471-2350-6-24
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HFEgenetic testing on clinical presentation of hereditary hemochromatosis: new epidemiological data

Abstract: BackgroundHereditary hemochromatosis (HH) is a common inherited disorder of iron metabolism in Northern European populations. The discovery of a candidate gene in 1996 (HFE), and of its main mutation (C282Y), has radically altered the way to diagnose this disease. The aim of this study was to assess the impact of the HFE gene discovery on the clinical presentation and epidemiology of HH.MethodsWe studied our cohort of 415 patients homozygous for the C282Y allele and included in a phlebotomy program in a blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 49 publications
2
26
0
1
Order By: Relevance
“…We have recently shown that HFE C282Y mutation testing has modified the epidemiology of haemochromatosis, with the sex ratio reduced to close to 1.0 and a weaker clinical expression than observed previously. 132 However, we should also be aware that the C282Y homozygous genotype is not fully penetrant and that its expression depends on the complex interplay of genetic and nongenetic factors. Several investigations are focusing on discovery of the genetic factors that enable us to identify more precisely those C282Y homozygous patients at increased risk of developing clinical features.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that HFE C282Y mutation testing has modified the epidemiology of haemochromatosis, with the sex ratio reduced to close to 1.0 and a weaker clinical expression than observed previously. 132 However, we should also be aware that the C282Y homozygous genotype is not fully penetrant and that its expression depends on the complex interplay of genetic and nongenetic factors. Several investigations are focusing on discovery of the genetic factors that enable us to identify more precisely those C282Y homozygous patients at increased risk of developing clinical features.…”
Section: Resultsmentioning
confidence: 99%
“…3,5 As it was expected, when assessed together, there was no statistical difference in the genotypic frequencies of C282Y and H63D between genders due to the fact that both are autosomally inherited.…”
Section: Discussionmentioning
confidence: 60%
“…2,3,4 It is unquestionable that C282Y is the main mutation responsible for HH in all studied populations, as the majority of published reports worldwide cite its prevalence in more than 80% of individuals with clinical manifestations of HH, 1,[4][5][6]12,15,17,23 thus several other diagnostic guides are based on the result of C282Y mutation genic testing. 2,6,7,15 It is not different for the Brazilian population, as in the paper by Bittencourt et al, 1 homozygous individuals for this mutation present an earlier onset for pathological aspects compared to heterozygous individuals with an onset at an earlier age than the wild allele, 282CC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations